Synthesis of colloidal nanoparticles CdS:Mn in the polymer solution for biological applications - Fediv, V.I.; Rudko, G.Yu.; Savchuk, A.I.; Gule, E.G.; Davydenko, I.S. (Functional Materials, 2014)
Kinetics of the colloidal CdS:Mn nanoparticles synthesis in the solutions of polyvinyl pirrolidone and mixture of polyvinyl pirrolidone with polyvinyl alcohol is studied by optical absorption method. The dependences of NPs size, polydispersity index and concentration of NPs on the precursors concentration in the growth solution are studied. The factors that affect the characteristics of colloidal nanoparticles are analyzed. It is shown that growing in the mixture of macromolecules improves the synthesis kinetics and provides stabilization of the average nanoparticles size in wide range of precursors concentration. The possibility to use the colloidal solutions polymer/nano-CdS:Mn as light-emitting labels in whole blood was demonstrated.